RANCANG BANGUN SISTEM PELACAK KENDARAAN MENGGUNAKAN GPS DAN GSM BERBASIS ARDUINO NANO - Muhammad Fadhurrahman; Elvan Yuniarti; Dewi lestari (Universitas Riau, 2021)
Vehicle theft rates in Bekasi City are still high. Only about 22.7% cases have been successfully solved. The main problem is hard to track vehicles because too many vehicles in the city of Bekasi. The aims of this research is to design and build a vehicle tracking system using GPS, GSM, Relay, and Arduino Nano. The test was performed by measuring the length of time it takes for GPS device to locks the signal satellite, receive and send a short message to vehicle’s owner. The result was succeeded in designing and building vehicle tracking system using GPS, GSM, and Arduino Nano with a relay as a support to make the vehicle stay in an off condition and can trigger an alarm sound so it can easily to find the location of the vehicle. GPS device has an average time delay of locking a signal for 196 seconds at daylight and 72 seconds at night with accuracy for amount 95.33%. Tracker device has an average time delay for sending message to user at 13.82 seconds for different mobile’s operator and 11.60 seconds for the same mobile’s operator with accuracy for amount 70.73%.